2010
DOI: 10.1089/hum.2009.202
|View full text |Cite
|
Sign up to set email alerts
|

CD40-Targeted Recombinant Adenovirus Significantly Enhances the Efficacy of Antitumor Vaccines Based on Dendritic Cells and B Cells

Abstract: Despite the advantages of using adenoviral vectors for specific antigenic gene delivery in the development of antigen-presenting cell (APC)-based vaccines, the lack of the coxsackievirus-adenovirus receptor (CAR) on APCs limits the use of adenoviral vectors for in vitro gene delivery. In this study, we used a recombinant adapter protein, CFm40L, which consists of the ectodomain of CAR genetically fused to the ectodomain of CD40 ligand (CD40L) via a trimerization motif, to target Her-2/neu- or human papillomavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…To this end, we employed a B-cell-based antitumor vaccine (31,32). We have convincingly showed that a NKT ligand-loaded, B-cell-based vaccine elicits tumor-specific immune responses (21,33,34). We subcutaneously inoculated Balb/c mice with CT26 tumor cells on day 0 and then intraperitoneally injected the mice with 0.5 mg of antiosteopontin (MPIIIB10) or mIgG as a control every other day for 10 days (Fig.…”
Section: Antiosteopontin Enhances Antitumor Therapeutic Effect Of Celmentioning
confidence: 99%
“…To this end, we employed a B-cell-based antitumor vaccine (31,32). We have convincingly showed that a NKT ligand-loaded, B-cell-based vaccine elicits tumor-specific immune responses (21,33,34). We subcutaneously inoculated Balb/c mice with CT26 tumor cells on day 0 and then intraperitoneally injected the mice with 0.5 mg of antiosteopontin (MPIIIB10) or mIgG as a control every other day for 10 days (Fig.…”
Section: Antiosteopontin Enhances Antitumor Therapeutic Effect Of Celmentioning
confidence: 99%
“…Several groups have investigated the potential of CD40L as a molecular adjuvant by either codelivering CD40L with Ags (13)(14)(15)(16)(17)(18)(19)(20) or retargeting the Ag-delivery vector to CD40 on APCs (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Although enhanced immune responses against various pathogens and tumors were observed, little is known about in vivo B cell responses, functional roles of CD4 + and CD8 + T cells during induction phase, or the contributions of Abs and CD8 + T cells in protection.…”
mentioning
confidence: 99%
“…The efficacy of ex vivo loaded DCs, which are often used as cancer vaccines (43), may be improved upon by transduction with CD40-Ad (17,44). This approach is however wrought with issues about logistics and consistency; in vivo targeting of antigens to DCs would instead allow for a more standardized vaccination method (5).…”
Section: Discussionmentioning
confidence: 99%